Concussion : assessment, management and rehabilitation - Blessen C. Eapen; David X. Cifu ([Philadelphia, Pa.] : Elsevier, 2020)
This practical reference, edited by Drs. Blessen C. Eapen and David X. Cifu, covers the full spectrum of assessment, management, and rehabilitation after concussion. It includes best practices and considerations for numerous patient populations and their unique needs in an easy-to-read, concise format. Geared toward physiatrists, neurologists, primary care physicians, and rehabilitation professionals, this book provides the key information you need to guide your treatment plans and help patients recover after concussion.
Keywords: Brain Concussion Diagnosis; Post-Concussion Syndrome; Brain Concussion therapy